Pesantren and Liberating Education: A Case Study at Islamic Boarding School ISC Aswaja Lintang Songo Piyungan Yogyakarta - Ahmad Shofiyuddin Ichsan; Samsudin Samsudin; Nindya Rachman Pranajati (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
This research aims to explain how the existence of Islamic Boarding School (pesantren) ISC Aswaja Lintang Songo Piyungan Yogyakarta in implementing education that liberates its students and how progressivism views a liberating education in this pesantren. This research is naturalistic qualitative research and the strategy used is a case study. At the same time, these research objects are a pesantren leader (kiai) and several senior teachers. The data obtained through observations, interviews, and documentation. The data analysis technique uses the Miles and Huberman model analysis. This research indicates that independent education in this pesantren is the starting point for implementing liberating education. This pesantren has an education system which is different from other pesantren, in that kiai gives liberation for their students (santri) to choose activities inside and outside pesantren. Therefore, in the view of progressivism, there are at least five things seen from the education process in this pesantren, namely 1). Kiai does not use their leadership in an authoritarian manner, 2). Kiai never carries out an exclusive educational process, 3). Kiai gives flexibility to santri in understanding Islamic education material, 4). Pesantren education has to continue to be open to social realities, and 5). The educational process carried out in pesantren is education of individual and social awareness.